Letter from Lillian Roman to Jane Tolmach - Lillian Roman:::::: (1974)
A letter fro Lillian Roman, the Assistant Vice President of Hacienda Federal Savings and Loan Association, to Jane Tolmach congratulating her on her reelection to the Oxnard City Council.